2022
DOI: 10.1101/2022.11.29.518068
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Selective whole-genome sequencing ofPlasmodiumparasites directly from blood samples by Nanopore adaptive sampling

Abstract: BackgroundWhole-genome sequencing (WGS) is becoming an increasingly popular tool to study the population genetics and drug resistance ofPlasmodiumspp. However, the predominance of human DNA in a malaria patient blood sample requires time-consuming lab procedures to filter out human DNA or enrichPlasmodiumDNA. Here, we investigated the potential of adaptive sampling to enrich forPlasmodiumDNA while sequencing unenriched patient blood samples on a minION device.ResultsTo compare adaptive sampling versus regular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…We obtained an enrichment by yield up to 3.7 times on average and an enrichment by selection up to 69 times on average, even when the reference was genetically distant from the sequenced accession. These findings are comparable to the best results previously obtained enriching individuals in metagenomics samples (De Meulenaere et al, 2022;Martin et al, 2022) and outperformed the enrichment values previously obtained with loci panels (Hogers et al, 2020). The successful enrichment with NAS could be linked to the percentage of the genome targeted here (~1.41%), the size of the targets, or the size of the DNA fragments, as they have been demonstrated to be main factors of enrichment rate (Martin et al, 2022;Community Nanopore, 2023).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We obtained an enrichment by yield up to 3.7 times on average and an enrichment by selection up to 69 times on average, even when the reference was genetically distant from the sequenced accession. These findings are comparable to the best results previously obtained enriching individuals in metagenomics samples (De Meulenaere et al, 2022;Martin et al, 2022) and outperformed the enrichment values previously obtained with loci panels (Hogers et al, 2020). The successful enrichment with NAS could be linked to the percentage of the genome targeted here (~1.41%), the size of the targets, or the size of the DNA fragments, as they have been demonstrated to be main factors of enrichment rate (Martin et al, 2022;Community Nanopore, 2023).…”
Section: Discussionsupporting
confidence: 90%
“…One key factor that largely affects final yield in ONT sequencing runs is the number of active channels at the beginning of the run and their lifespan, which may significantly differ from one flowcell to another. Therefore, we implemented a half-flowcell design to compare NAS and WGS eliminating biases that may arise when using two different flowcells, as previously settled in many studies (De Meulenaere et al, 2022; Martin et al, 2022). Results showed that for both Anso77 and Doublon, NAS produced about four times more on-target data than WGS (Table 3), while generating about ten times less total data (see filtered NAS and WGS in Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the here used combination of long-read sequencing and a low-input material approach, might facilitate assembly of P. vivax field isolates from blood volumes as small as a finger prick. In addition, Oxford Nanopore’s portable sequencer could become a quick and easy to use alternative for PacBio sequencing (De Meulenaere et al, 2022a), given further improvements in accuracy and DNA input requirements.…”
Section: Discussionmentioning
confidence: 99%
“…1-2kbp). Moreover, work on adaptive sampling of reads during nanopore sequencing has recently been applied to P. falciparum malaria 61 , and variations of this approach may help recover better data from low parasitemia samples.…”
Section: /31mentioning
confidence: 99%